Clinical response to golimumab in rheumatoid arthritis patients who were receiving etanercept or adalimumab: results of a multicenter active treatment study. (3rd April 2017) - Huffstutter, Joseph E.; Kafka, Shelly; Brent, Lawrence H.; Matucci-Cerinic, Marco; Tang, Kezhen L.; Chevrier, Marc; Sprabery, Trev; DeHoratius, Raphael J.
Abstract: Objective: Evaluate the efficacy and safety of subcutaneous (SC) golimumab + methotrexate (MTX) in patients with active rheumatoid arthritis (RA) despite etanercept + MTX or adalimumab + MTX therapy and evaluate whether intravenous (IV) golimumab could rescue patients who were nonresponders to SC golimumab. Methods: In this multicenter, assessor-blinded, active-switch study of patients with RA ( n = 433) with inadequate response to etanercept or adalimumab + MTX, patients continued MTX and received open-label SC golimumab 50 mg every 4 weeks through week 12. DAS28-ESR good responders at week 16 continued open-label SC golimumab through week 52 (Group 1); nonresponders were randomized to double-blind golimumab SC 50 mg (Group 2-SC) or IV 2 mg/kg (Group 2-IV). Week 14 ACR20 was the primary endpoint; assessments continued through week 52 and for patients in the voluntary long-term extension through week 76. A major secondary endpoint was the proportions of patients with ACR20 response at week 52 relative to week 16 in Group 2-SC and Group 2-IV. Results: At week 14, 34.9% ( p < 0.001) achieved an ACR20. At week 52, patients in Group 1 ( n = 75) achieved an ACR20 (62.7%). In Groups 2-SC ( n = 91) and 2-IV ( n = 184), 13.2% and 9.2% had an ACR20 at week 52 relative to week 16, with no significant difference between the randomized groups; 42.9% and 47.8% achieved DAS28-ESR response relative to week 0. Through week 16, 4.6% of patients had a serious adverse event. No differences in the rates or types of adverse events were observed between SC and IV golimumab from weeks 16 to 52. The trial limitations included a higher than expected discontinuation rate as a result of a programming error. Conclusion: SC golimumab + MTX significantly suppressed disease activity in RA patients with inadequate response to etanercept and/or adalimumab + MTX. Patients randomized to Groups 2-SC and 2-IV had lower response rates than Group 1, with no difference between SC or IV mode of administration. The safety profile with IV golimumab was comparable to that established with SC golimumab. Trial registration: NCT01004432, EudraCT 2009-010582-23.